2015
DOI: 10.4315/0362-028x.jfp-14-095
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Survey of Indicator and Pathogenic Bacteria on Vegetables Sold from Asian Vendors at Farmers’ Markets in Northern California

Abstract: A cross-sectional survey was conducted during summer 2013 to determine the occurrence of Escherichia coli, fecal coliforms (FCs), E. coli O157:H7, and Salmonella on raw vegetable commodities common to Asian cuisine from 21 vendors or farmers at six farmers' markets in northern California. Based on 242 samples from six commodities (basil, yardlong beans, bitter squash, okra, squash stems and leaves, cilantro), 100% of samples had detectable FCs and 20% had detectable E. coli. The mean concentrations were 0.67 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…Because the presence of E. coli in fruits indicates possible fecal contamination during harvesting and/or handling, these findings should be taken seriously given that pathogenic E. coli O157:H7 often can come from the same contamination sources (Aslam et al, 2003; Fegan, Higgs, Vanderlinde, & Desmarchelier, 2003). Regardless of plant part classifications, the overall prevalence (9.4%) of E. coli obtained in our study was considerably lower than a study conducted by Pan et al (2015), which detected E. coli in 20% of 242 commodities including basil, beans, squash, okra, and cilantro obtained from farmers' markets in Northern California. Additionally, a recent survey (Scheinberg et al, 2017) in Pennsylvania, where a total of 152 samples of leafy vegetables including kale, lettuce and spinach obtained from farmers' markets were analyzed, detected the prevalence of E. coli in 25% of samples.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…Because the presence of E. coli in fruits indicates possible fecal contamination during harvesting and/or handling, these findings should be taken seriously given that pathogenic E. coli O157:H7 often can come from the same contamination sources (Aslam et al, 2003; Fegan, Higgs, Vanderlinde, & Desmarchelier, 2003). Regardless of plant part classifications, the overall prevalence (9.4%) of E. coli obtained in our study was considerably lower than a study conducted by Pan et al (2015), which detected E. coli in 20% of 242 commodities including basil, beans, squash, okra, and cilantro obtained from farmers' markets in Northern California. Additionally, a recent survey (Scheinberg et al, 2017) in Pennsylvania, where a total of 152 samples of leafy vegetables including kale, lettuce and spinach obtained from farmers' markets were analyzed, detected the prevalence of E. coli in 25% of samples.…”
Section: Resultscontrasting
confidence: 89%
“…A prevalence study on 261 leafy green commodities obtained from the central coast of California also found no detectable Salmonella (Gorski et al, 2011). In contrast, a study conducted by Pan et al (2015) reported the presence of Salmonella in 6.6% of 242 fresh produce commodities. In another related study, Levy et al (2015) reported that prevalence of Salmonella was detected in 0.8% of 133 fresh herb samples obtained from 13 farmers' markets in Los Angeles, CA and Seattle, WA.…”
Section: Resultsmentioning
confidence: 87%
“…Subsequently, mixed-effects negative binomial regression models were performed to predict the concentrations of E. coli in Model A of oyster and Model C of estuarine water. The negative binomial regression model is suitable for overly dispersed count data, and this method has been widely used in microbiological studies, such as pre-harvest contamination of indicator and pathogenic bacteria in mixed produce, and the impact of farm management and environmental factors on the level of indicator bacteria in spinach [34,35,36]. Furthermore, more advanced studies on diversity of microbial ecological interaction networks on metagenomic data and microbiome count data have also used negative binomial regression to generate proper statistical models [37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Farmers markets contain a variety of goods, both raw and RTE, which regularly change with the seasons (69,98). Many such goods sold at farmers markets, like leafy greens, vegetables, and fruits, have been consistently found to be contaminated with pathogens like L. monocytogenes, pathogenic E. coli, and Salmonella spp.…”
Section: Atypical Cross-contamination Venuesmentioning
confidence: 99%
“…Many such goods sold at farmers markets, like leafy greens, vegetables, and fruits, have been consistently found to be contaminated with pathogens like L. monocytogenes, pathogenic E. coli, and Salmonella spp. (69,98). These goods must be stored and displayed in containers or on tables provided by the farmer or retailer.…”
Section: Atypical Cross-contamination Venuesmentioning
confidence: 99%